The management of large vessel vasculitides - Elena Galli; Chiara Marvisi; Gilda Sandri; Carlo Umberto Manzini; Carlo Salvarani (Verduci Editore, 2021)
Giant cell arteritis (GCA) and Takayasu arteritis (TAK) represent the most common large vessel vasculitides (LVV). An early recognition of these conditions is crucial in order to start a prompt treatment to prevent severe ischemic complications, such as irreversible visual loss in GCA and cardiovascular or cerebrovascular accidents in TAK. Isolated glucocorticoids (GCs) still remain the cornerstone of GCA therapy. However, long-term treatment with GCs is burdened by an important toxicity. Furthermore, relapses are frequent during the follow-up period and relapsing patients have to cope with a longer duration of the GC therapy and a higher cumulative GC dose. On the other hand, TAK treatment usually relies on immunosuppressors in addition to GCs from the beginning. Also, since TAK patients are in general young women with a progressive disease, it is essential to treat this vasculitis with steroidsparing drugs in order to avoid excessive GC exposure. For this reason, efforts have been made to discover new therapeutic options able to reduce the cumulative GC dose that is strictly related to GC-toxicity. In recent years, new advances in the management of LVV have become available and have changed the therapeutic approach to these diseases. The aim of this review is to report new evidence of treatment efficacy and safety in LVV.